TRADISI MENGGUNAKAN JASA PAWANG HUJAN DITINJAU DARI AQIDAH ISLAM - Arifinsyah Arifinsyah; Salahuddin Harahap; Sapitri Yuliani (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
According to the Sei Rotan Village Community, Pawang Hujan is someone who is good at moving or controlling rain using masical or supernatural science which is carried out by means of rituals using several requirements such as fresh red chillies that still have stems, salt, and nails. Provided by the person who is doing the celebration. According to the belief of the Sei Rotan village community, for people who want to do a celebration event or a wedding party, you should use the services of a rain handler for the smooth running of the eent without any obstacles because of the coming rain. The purpose of study is to see whether the use of the services of the rain handler and how the procedure of the implementation of this rain handler deviates from the Islamic aqeedah which can lead to acts of shirk towards Allah that we should make a place to ask for any help. The type of this thesis research is a qualitative research model with descriptive methods by means of observation or observing whether the tradition of using the services of this rain handler deviates from islamic aqidah as the purpose of this thesis is made. Keywords: Tradition, Rain Handler, Aqidah Islamic Review.